INTEGRATED INFORMATION SYSTEM DEVELOPMENT OF UIN RADEN INTAN LAMPUNG - Husaini, Muhammad (KOMUNIKA, 2019)
The rapid development of information technology (IT) supported inexpensive of infrastructure supply results in tight competition between profit and non-profit organizations. In fact, however, many of them in investment of IT supply meet the failures. Instead of increase the performance, they must be back into the manual system after release the investment. Immature in the development planning of IT and do not exist a strategic planning of information system development of organization which become information system development road map, led to these failures. The planning orientation is incomplete and it is based on the temporary demand or particular function of organization, which it result in disintegration between developed systems. Support of information system development road map contain rules, actions and management to obtain the vision and mission of organization in the development of integrated information system, is expected to minimize a potential failure. By integrated information system development road map In UIN Raden Intan Lampung it expected that the system development will moves in continuously, intended and integrated to create the competitive advantage of organization. The compilation process of integrated information system development road map is started by analysis in organization area, whether in internal or external. The analysis result is used as input in formulation of organizational IS/IT strategy. From the analysis result above, it can know the opportunity, threat and organizational potency to reach competitive advantage based on IT. By identifying critical factors which play an important rule to attain the vision and mission by IT, it can be arranged a related application portfolio to the organization. The analysis is supported by , SWOT analysis and CSF Analysis. The contribution of application portofolio which have been formed to attain organizational vision and mission must be studied. subdividing application portofolio pursuant to its contribution to attain organizational vision and mission can make application portofolio development project measured and in harmony  with the condition and target of organization. subdividing application portofilo pursuant to its contribution to organization. The proposed strategy for integrated information system development in UIN Raden Intan Lampung is used an in-source development strategy. It is used to complete the previous suggested method. By the strategy, it expected that development process of integrated information system in UIN Raden Intan Lampung will provides a contribution for academic.